2013
DOI: 10.1002/msc.1061
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Expectations, Experiences and the Determinants of Satisfaction related to Metacarpophalangeal Arthroplasty

Abstract: Joint goal-setting is essential for understanding patients' unique reasons for undergoing MCP arthroplasty and facilitating realistic expectations. Education on all aspects of postoperative care is vital. Patients should be made aware of variability in outcome and the potential for deterioration due to the chronic nature of rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It has been previously shown that fulfillment of expectations seems to be one of the most important factors of postoperative satisfaction following hand surgery. 25 26 27 28 Surgeon factors and patient-specific factors such as employment or marital status may also play a role in satisfaction, although it was interesting to note that these factors were not significantly associated with expectations in our study. Furthermore, coexisting mental health conditions could impact satisfaction through a psychiatric lens.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…It has been previously shown that fulfillment of expectations seems to be one of the most important factors of postoperative satisfaction following hand surgery. 25 26 27 28 Surgeon factors and patient-specific factors such as employment or marital status may also play a role in satisfaction, although it was interesting to note that these factors were not significantly associated with expectations in our study. Furthermore, coexisting mental health conditions could impact satisfaction through a psychiatric lens.…”
Section: Discussionmentioning
confidence: 53%
“…Because of these points, making sure that comprehensive, individualized, and realistic expectations are communicated to the patient prior to surgery is imperative. 26,27,[49][50][51] This will help ensure that the patient has balanced expectations of the outcome, and can help prevent dissatisfaction despite a "successful" surgery. This has been discussed in many different surgical populations [11][12][13][14]22,32,52 and is an important trend in orthopaedic surgery with the recent emphasis on PROs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important outcomes metric for hand surgery is the concept of expectation. Studies have shown that outcomes are generally better when patients’ expectations are high but rational (Lutz et al, 1999; Sharrock et al, 2013). By applying psychometric principles in developing expectation questionnaires in hand surgery, hand surgeons can better link the elusive outcomes goal of patient satisfaction as a new dimension of outcomes research.…”
mentioning
confidence: 99%